2015
DOI: 10.1371/journal.pntd.0003936
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Leishmania (Viannia) Kinetoplast DNA in Ulcers of Cutaneous Leishmaniasis Reveals Inter-site and Inter-sampling Variability in Parasite Load

Abstract: BackgroundCutaneous leishmaniasis (CL) is a skin disease caused by the protozoan parasite Leishmania. Few studies have assessed the influence of the sample collection site within the ulcer and the sampling method on the sensitivity of parasitological and molecular diagnostic techniques for CL. Sensitivity of the technique can be dependent upon the load and distribution of Leishmania amastigotes in the lesion.Methodology/Principal FindingsWe applied a quantitative real-time PCR (qPCR) assay for Leishmania (Vian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 46 publications
3
47
2
4
Order By: Relevance
“…Additionally, in the present study, swabs and biopsy samples had similar sensitivity values when the same chemistry was used for qPCR. These findings are in contrast to the higher accuracy of swab analysis in CL reported in previous studies (12,13,18).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Additionally, in the present study, swabs and biopsy samples had similar sensitivity values when the same chemistry was used for qPCR. These findings are in contrast to the higher accuracy of swab analysis in CL reported in previous studies (12,13,18).…”
Section: Discussioncontrasting
confidence: 99%
“…Swabs and cytology brush samples of localized cutaneous leishmaniasis (CL) are more sensitive than lesion aspirate and biopsy samples (12,13). The utility of swabbased diagnosis in mucosal leishmaniasis (ML) has not been completely explored, as most studies have been conducted in highly controlled environments, usually using healthy controls for comparison (5).…”
mentioning
confidence: 99%
“…Weigle and others showed that PCR sensitivity was higher than the conventional assays for the diagnosis of acute lesions while for chronic samples, the sensitivity of PCR was much higher than the conventional assays (27). and number or area of lesions, there was no difference in parasite load (30). Sirian and co-workers conducted a comparison between conventional, molecular, and immunohistochemical methods for CL detection and reported that immunohistochemical and molecular techniques were more sensitive (31)(32)(33).…”
Section: Resultsmentioning
confidence: 98%
“…Leishmania (Viannia) parasites. According to the parasite species, the patients' age, and number or area of lesions, there was no difference in parasite load (30). Sirian and co-workers conducted a comparison between conventional, molecular, and immunohistochemical methods for CL detection and reported that immunohistochemical and molecular techniques were more sensitive (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, PCR-based testing of skin lesion biopsies is known as a sensitive and specific test for diagnosis and quantification of leishmaniasis (13)(14)(15)(16). The analysis of the load of leishmania parasites within the skin lesions would be important not only for diagnostic purposes, but also for an eventual follow-up of a patient's response to treatment (17). Accordingly, in the present study we applied a standardized qPCR assay to detect Leishmania.…”
Section: Introductionmentioning
confidence: 99%